ÑAMSAPA AND HIS LIEUTENANT - Hocquenghem, Anne Marie (2011)
Using Gerald Taylor’s translation of chapter 24 of the Huarochiri quechua manuscript from the beginning of the XVII century, as well as his comments and notes to this text, the aim is to identify the attributes of Ñamsapa, progenitor of the checas, and evidence the symbolic, metonymic, relation established between this objects and who exhibit them. Comparing the Huarochiri indians traditions with the myths and rituals figuring in prehispanic iconographies, particularly mochica, it is intended to show that the narratives as well as the images relate to the same cosmovision, religion and Andean civilization, old of tree millenniums.